NURSE RETENTION STRATEGY AT ADVENT HOSPITAL MEDAN WITH SWOT APPROACH (STRENGTHS, WEAKNESSES, OPPORTUNITIES, THREATS) - Yohanna Arminta Zega; Yeni Absah; T. Sabrina (CV. Radja Publika, 2025)
The growth and development of health care facilities require hospitals to be able to retain quality nursing staff to ensure the continuity of optimal services. Medan Adventist Hospital as one of the private health institutions in the Medan area faces challenges in maintaining the number and quality of competent and highly committed nurses. Therefore, this study aims to identify factors that influence nurse retention and develop effective strategies using the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach. The research method used is qualitative with a case study approach, collecting data through in-depth interviews, direct observation, and distributing questionnaires to nurses and hospital management. The data obtained were analyzed using SWOT analysis to determine internal strengths, internal weaknesses, external opportunities, and external threats in the context of nursing staff retention at Medan Adventist Hospital. The results of the analysis show that the main strengths of the hospital include adequate service facilities and competency development programs, while its weaknesses include uncompetitive incentive levels and working conditions that result in job dissatisfaction. On the opportunity side, technological developments and the public's need for quality health services open up opportunities for innovation and quality improvement, while threats come from other competitors and high levels of workforce turnover. Based on these results, several strategies are recommended, including improving incentive and benefit programs, improving working conditions and work environment, improving competency and training on an ongoing basis, and strengthening communication and involvement of nurses in decision making. This strategy is expected to increase nurse motivation and loyalty so as to strengthen the retention of nursing staff at Medan Adventist Hospital and ultimately improve the quality of health services provided to the community.